Sportivnaya trenirivka: upravlenie, sistemnost', adaptatsiya, zdorov'e - Kulikov, L. M.; Velikaya, E. A.; Rybakov, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to analyse the system "organism - environment" with a help of the integrative approach to the objective display, measuring and evaluation of this system for the realization of the obtained results in the process of sports training managing. 250 athletes of national and international level aged from 17 to 28 acted as subjects of the longitude experiments at the period 1985-1995. Theoretical, pedagogical, physiological, biochemical and clinical methods of investigation had been used.